Elderly homicide in Chicago: a research note. - Fazel, S; Bond, M; Gulati, G; O'Donnell, I (2007)
There is a body of knowledge about elderly crime victims, but we know little about the characteristics of elderly perpetrators, especially of homicide. The few studies that have been published are based on small samples and are somewhat dated. In an examination of homicides committed in Chicago over a 31-year period, we compared cases involving perpetrators aged over 60 years (n = 443) with those involving younger perpetrators (n = 24,066). There were a number of significant differences. Elderly killers were more likely to be White and to commit suicide afterwards. Their victims were more likely to be spouses, females, and aged over 60 years. Inter-racial homicide was more common for younger offenders. The low number of homicides involving the elderly is explained by reference to routine activity theory.